Perpustakaan sebagai Media Komunikasi Ilmiah - Ruhimat; Umam, Muthiara Sjahrani (JURNAL KOMUNIKATIO, 2025)
Scientific communication and dissemination of knowledge have been done for a long time. This paper will discuss the role and efforts of college libraries in building institutions that provide information and as a tool for scientific communication, as well as in managing institutional repository collections that change communication media. The purpose of this study is to find out and provide options for services available in college libraries, especially in the Djuanda University Library. Scientific communication is communication that occurs between scientists in certain fields, such as notification, transfer, dissemination, and dissemination of information in the form of books and other types of information. College libraries are one of the media for scientific communication for educational institutions, research, and publishing. This scientific communication can be built through communication between librarians and users, lecturers, students, and experts. And these findings indicate that research on the media used by libraries for scientific communication must continue to be carried out. The Djuanda University Library is an organization that has space to support the advancement of science. Keywords: Scientific communication; Library; E-Print; Djuanda University